Modeling the influence of deep water application of dispersants on the surface expression of oil: A sensitivity study. Issue 8 (19th August 2016) - Testa, Jeremy M.; Eric Adams, E.; North, Elizabeth W.; He, Ruoying
Abstract: Although the effects of chemical dispersants on oil droplet sizes and ascent speeds are well‐known, the fate and transport of dispersed oil droplets of different sizes under varying hydrodynamic conditions can be difficult to assess with observations alone. We used a particle tracking model to evaluate the effect of changes in droplet sizes due to dispersant application on the short‐term transport and surface expression of oil released under conditions similar to those following the 3 June 2010 riser cutting during the Deepwater Horizon event. We used simulated injections of oil droplets of varying size and number under conditions associated with no dispersant application and with dispersant application at 50% and 100% efficiency. Due to larger droplet sizes in the no‐dispersant scenario, all of the simulated oil reached the surface within 7 h, while only 61% and 28% of the oil reached the surface after 12 h in the 50% and 100% dispersant efficiency cases, respectively. The length of the surface slick after 6 h was ∼2 km in the no‐dispersant case whereas there was no surface slick after 6 h in the 100% dispersant case, because the smaller oil droplets which resulted from dispersant application had not yet reached the surface. Model results suggest that the application of dispersants at the well head had the following effects: (1) less oil reached the surface in the 6‐12 h after application, (2) oil had a longer residence time in the water‐column, and (3) oil was more highly influenced by subsurface transport. Key Points: Numerical models are useful for examining the sensitivity of oil fate and transport to dispersant application Simulated dispersant application strongly influenced the timing and spatial extent of surfacing oil Simulated dispersant application resulted in slower oil surfacing time and higher subsurface retention